1987
DOI: 10.1038/jcbfm.1987.138
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Effects on Local Cerebral Blood Flow and Metabolism in the Rat

Abstract: The effects of an anesthetic dose (100 mg/kg) of ketamine, a phencyclidine derivative, on local rates of cerebral glucose utilization (LCGU) and CBF (LCBF) have been investigated by the quantitative [14C]2-deoxy-glucose and [14C]iodoantipyrine techniques in the unparalyzed, spontaneously breathing rat. In ketamine-injected animals, LCGU was significantly increased in some limbic structures and decreased in inferior colliculus, vestibular, and cerebellar nuclei. The degree and spatial distribution of drug-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
3

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 36 publications
1
55
1
3
Order By: Relevance
“…Several lines of evidence support the suggestion that the observed pattern of activation is representative of the central effects of PCP in freely moving animals and in humans. First, the observation of activation in response to PCP is consistent with the excitatory effects of NMDAR antagonists observed in freely moving rodents, measured with single unit recording (Homayoun et al, 2005), [ 14 C]-iodoantipyrine CBF measurements (Cavazzuti et al, 1987), and 2DG Duncan et al, 1998aDuncan et al, , b, 1999bDuncan et al, , 2000Weissman et al, 1987;Meibach et al, 1979). Second, the anatomical distribution of rCBV changes is consistent with regions of increased 2DG uptake in conscious rats upon injection of NMDAr antagonist such as PCP, ketamine, or MK-801 (Duncan et al, 1999a).…”
Section: Drug Modulation Of Phmri Response To Pcpsupporting
confidence: 70%
“…Several lines of evidence support the suggestion that the observed pattern of activation is representative of the central effects of PCP in freely moving animals and in humans. First, the observation of activation in response to PCP is consistent with the excitatory effects of NMDAR antagonists observed in freely moving rodents, measured with single unit recording (Homayoun et al, 2005), [ 14 C]-iodoantipyrine CBF measurements (Cavazzuti et al, 1987), and 2DG Duncan et al, 1998aDuncan et al, , b, 1999bDuncan et al, , 2000Weissman et al, 1987;Meibach et al, 1979). Second, the anatomical distribution of rCBV changes is consistent with regions of increased 2DG uptake in conscious rats upon injection of NMDAr antagonist such as PCP, ketamine, or MK-801 (Duncan et al, 1999a).…”
Section: Drug Modulation Of Phmri Response To Pcpsupporting
confidence: 70%
“…However, recent investigations showed that ketamine or its enantiomere S(+)-ketamine meets most of the above mentioned criteria: ketamine as a single anesthetic or in combination with benzodiazepines, propofol or isoflurane does not affect ICP 1-3 or the coupling between CBF and CMR. 4 Likewise, recovery of postoperative psychomotor function and performance was more rapid with the enantiomere S(+)-ketamine compared to racemic ketamine. 5 In animal models of cerebral ischemia and traumatic head injury ketamine and its enantiomere S(+)-ketamine showed brain protective potential even when administered one hour after the insult.…”
Section: Discussionmentioning
confidence: 96%
“…Heightened blood flow may remove lactate accumulated as a result of the maintenance of intracellular ionic homeostasis by glycolysis during the intense activation of cingulate neurones. Interestingly, following ketamine administration, cerebral blood flow was also found to increase in excess of metabolic demand within the cingulate cortex (Cavazzuti et al, 1987).…”
Section: Discussionmentioning
confidence: 99%